Talfīq as a Legal Solution in Modern Hajj Jurisprudence - Nasharuddin, Nur Ain Nabihah; Salleh, Ahmad Dahlan; Ramlee, Nurzakiah (al-'adalah, 2026)
Addressing challenges in the performance of Hajj is a critical priority, as this pilgrimage is conducted annually and involves millions of Muslims worldwide, including Malaysian Muslims. In recent times, the implementation of Hajj has faced a range of challenges, including overcrowding, evolving regulatory frameworks, and physical limitations, all of which call for a more flexible and realistic legal approach. Accordingly, this study aims to examine talfīq as an innovative and effective approach in resolving contemporary fiqh issues related to Hajj faced by Malaysian pilgrims. Talfīq refers to combining two opinions from different schools of thought or jurists. Although scholars differ in their opinions regarding the application of talfīq, modern developments indicate a growing acceptance of this method, especially when it serves legal necessity and public interest (maslahah). This study focuses on selected fiqh problems encountered by Malaysian pilgrims and proposes talfīq as a viable solution. This research employs a qualitative, literature-based methodology. Data sources include classical Islamic texts and relevant documents such as journal articles, contemporary fatwas, and resolutions from the National Hajj Muzakarah. The findings reveal that the method of talfīq has been applied in several Hajj-related fiqh issues, particularly in cases where there is no clear or practical opinion within the Shāfi’y school. Therefore, talfīq is seen as a beneficial legal approach to address current fiqh challenges in Hajj, especially for Malaysian pilgrims who follow the Shāfi’i school but require legal flexibility in certain circumstances